Factors Influencing Utilization of Cervical Cancer Screening Services in Kenya: The Case of Nyeri County - Gichogo Agnes Wangeci; David Macharia (International Journal of Public Health Science (IJPHS), 2018)
Globally, cervical cancer continues to be a major cause of mortality and morbidity among women with developing countries accounting for more than 86% of the deaths from the disease. In Kenya, cervical cancer ranks as the second most frequent cancer among women: regrettably, with 80% of the cases presented during the late stages of the disease when the scope of successful treatment is limited. An opportunity to prevent occurrence of cervical cancer exists through cervical cancer screening for early detection and treatment of precancerous lesions before these develop to cancer. However, only a negligible proportion of women benefit from cervical cancer screening services in developing countries, including Kenya. The purpose of this descriptive survey study was to determine the factors influencing utilization of cervical cancer screening services; and focused on the women seeking maternal and family planning services at Central Provincial General Hospital, Kenya. The study established that, as in most developing countries, utilization of cervical cancer screening services was low, regardless of the women’s education level, autonomy in decision making and even good family support. The low level of awareness on the need for screening services and the long waiting time at the clinic for those seeking the services were identified as the two key issues that negatively influenced the utilization of the screening services, It is therefore recommended that the Ministry of Health and other agencies, including individuals of good will, collaborate in designing and implementing awareness campaigns through the media and other appropriate avenues, including one-to-one encounters, targeting both men and women in the communities. It is also recommended that the male partners support their women in accessing this vital life-saving service.